Influence Recovery on Pattern Sleep Towards Female Basketball Athletes of MA Central Jakarta - Setiawan, Muhammad Arief; Aulia, Danny; Sentana, Bima; Saputra S, Misbahudin Nanda Agung; Putri, Ananda Mulia; Alkautsar, Fata Azima; Nabilahasha, Anggi (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research explores the impact of recovery on sleep patterns among female basketball athletes from MA Central Jakarta. Adequate sleep is essential for optimal physical and psychological performance, particularly in sports. Poor sleep patterns can lead to fatigue, decreased immune function, and suboptimal athletic performance. This study aims to assess the knowledge and habits of these athletes regarding sleep recovery and its implications for their performance. A descriptive statistical approach was utilized, involving a purposive sampling of 10 athletes aged 16-19 years. Data were collected using an online questionnaire with 18 structured questions focusing on sleep recovery patterns. The analysis employed the Guttman scale with binary responses (